Gambaran Efek Samping Oat Pada Pasien Tuberkulosis Paru Di Poli Paru Rsucm Aceh Utara - Maura Pulungan, Alyifia Yulia; Sahputri, Juwita; Rahmayani Siregar, Sarah (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
Tuberculosis (TB) is a infectious disease that remains a public health concern. The side effects of anti-TB drugs (ATDs) experienced by patients can affect the cure rate of tuberculosis. The purpose of this study was to determine the description of the side effects of ATDs use in pulmonary TB patients at the lung polyclinic of RSUCM North Aceh. This study used a quantitative descriptive research design with a cross-sectional approach. The sampling method used was purposive sampling with a total of 74 respondents. This research was conducted through interviews with patients using a questionnaire. From the interviews, it was found that the characteristics of pulmonary TB patients at the lung polyclinic of RSUCM North Aceh were mostly in the adult age category, which is 19-44 years old, male, had a high school education level, worked as farmers, already had a treatment supervisor (PMO), and with a duration of treatment of >2 months – 6 months. Furthermore, it was found that most patients experienced minor side effects. It can be concluded that most pulmonary TB patients at the lung polyclinic of RSUCM North Aceh experienced minor side effects of OAT. The most common side effect experienced by patients was redness in the urine, and the least common side effect experienced by patients was shock.